(untitled) (Development Service Industry Management, 2023)
The article is devoted to the study of the current state and trends in the development of photo tourism, an innovative direction of the development of the tourism sphere, which combines recreation, creativity and the use of photography as a means of remembering and expressing impressions. This topic examines the interaction between tourism activities and photography, which is a key element in the perception of travel, the innovative nature of photo tourism, its impact on the development of the tourism business, and the differences from traditional forms of travel. The role of social networks and technologies in the popularization of photo tourism and its influence on the formation of the cultural image of different regions is analyzed. In the process of research, the main indicators that characterize photo tourism and the state of its innovative environment in Ukraine were established. The work defines the theoretical and methodological principles of defining the concept and role of photography in tourism, the history of the development, and the content of the concept of "phototourism". The main regulatory and legal principles, innovative directions, and modern practices of photo tourism in the tourism sphere are analyzed. The world experience in the organization of photo tourism and the current state of development in this area is studied. Also, the tourism potential of Ukraine regarding the provision of photo services and the development of innovations was analyzed. In particular, the development of photo tourism and features of photo tours and their financial and economic indicators are characterized. Problems and prospects for developing photo tourism and ways to increase tourist opportunities in Ukraine have been identified. An innovative photo project in the Carpathian region "Through the Lens Prism" was developed.